Phenotypic characterization of peripheral T cells and their dynamics in scrub typhus patients. - Bon-A Cho; Youngho Ko; Yeon-Sook Kim; Sanguk Kim; Myung-Sik Choi; Ik-Sang Kim; Hang-Rae Kim; Nam-Hyuk Cho (PLoS Neglected Tropical Diseases)
Background Scrub typhus, caused by Orientia tsutsugamushi infection, is one of the main causes of febrile illness in the Asia-Pacific region. Although cell-mediated immunity plays an important role in protection, little is known about the phenotypic changes and dynamics of leukocytes in scrub typhus patients. Methodology/principal findings To reveal the underlying mechanisms of immunological pathogenesis, we extensively analyzed peripheral blood leukocytes, especially T cells, during acute and convalescent phases of infection in human patients and compared with healthy volunteers. We observed neutrophilia and CD4(+) T lymphopenia in the acute phase of infection, followed by proliferation of CD8(+) T cells during the convalescent phase. Massive T cell apoptosis was detected in the acute phase and preferential increase of CD8(+) T cells with activated phenotypes was observed in both acute and convalescent phases, which might be associated or correlated with elevated serum IL-7 and IL-15. Interestingly, peripheral Treg cells were significantly down-regulated throughout the disease course. Conclusions/significance The remarkable decrease of CD4(+) T cells, including Treg cells, during the acute phase of infection may contribute to the loss of immunological memory that are often observed in vaccine studies and recurrent human infection.